Carbohydrates in plant immunity and plant protection: roles and potential application as foliar sprays - Trouvelot, Sophie; Héloir, Marie-Claire; Poinssot, Benoît; Gauthier, Adrien; Paris, Franck; Guillier, Christelle; Combier, Maud; Trdá, Lucie; Daire, Xavier; Adrian, Marielle (Frontiers in Plant Science, 2014)
Increasing interest is devoted to carbohydrates for their roles in plant immunity. Some of them are elicitors of plant defenses whereas other ones act as signaling molecules in a manner similar to phytohormones. This review first describes the main classes of carbohydrates associated to plant immunity, their role and mode of action. More precisely, the state of the art about perception of “PAMP, MAMP and DAMP type” oligosaccharides is presented and examples of induced defense events are provided. A particular attention is paid to the structure / activity relationships of these compounds. The role of sugars as signaling molecules, especially in plant microbe interactions, is also presented. Secondly, the potentialities and limits of foliar sprays of carbohydrates to stimulate plant immunity for crop protection against diseases are discussed, with focus on the roles of the leaf cuticle and phyllosphere microflora.